Long noncoding RNA expression in peripheral blood mononuclear cells and suicide risk in Chinese patients with major depressive disorder. Issue 6 (2nd May 2017) - Cui, Xuelian; Niu, Wei; Kong, Lingming; He, Mingjun; Jiang, Kunhong; Chen, Shengdong; Zhong, Aifang; Li, Wanshuai; Lu, Jim; Zhang, Liyi
Abstract: Background: WHO stated that nearly one million people commit suicide every year worldly, and 40% of the suicide completer suffered from depression. The primary aim of this study was to explore the association between long noncoding RNAs (lncRNAs) expression in peripheral blood mononuclear cells (PBMCs) and suicide risk of patients with major depressive disorder (MDD). Methods: Using Human LncRNA 3.0 microarray profiling which includes 30, 586 human lncRNAs and RT‐PCR, six down‐regulated lncRNAs were identified differentially expressed in MDD patients. According to suicidal ideation and suicidal attempt, the suicide risk of MDD patients was classified into suicidal ideation versus no suicidal ideation groups, and past attempt versus no past attempt groups, respectively. The expression of six lncRNAs in MDD patients and controls were examined by RT‐PCR. Results: The expression of six lncRNAs had significant differences between no suicidal ideation, suicidal ideation, and controls; corresponding lncRNAs associated with suicidal attempt had remarkable differences between no past attempt, past attempt, and controls. Additionally, only the expression of lncRNAs in suicidal ideation group and past attempt group markedly declined compared with controls. Conclusions: This study indicated that the expression of six down‐regulated lncRNAs had a negative association with suicide risk in MDD patients, and the expression of lncRNAs in PBMCs could have the potential to help clinician judge the suicide risk of MDD patients to provide timely treatment and prevent suicide. Abstract : Epigenetics is the beginning of a new frontier in studies of complex diseases. Epigenetic modifications are reversible, and in a sense this modification is a dynamic process, allowing the cell to become more responsive to environment stimuli. Suicidal behavior includes a broad spectrum and many risk and protective factors. Suicide risk assessment is challenging for several reasons, so an objective and quantitative method is urgently needed. This study tried to explore the association between lncRNA expression in peripheral blood mononuclear cells with suicide risk level, and obtain a prediction equation.